Impaired exercise capacity in electrostatic polyester powder paint workers. (28th January 2021) - Sirayder, Ukbe; Inal-Ince, Deniz; Acik, Cihangir; Soyuer, Ferhan
Abstract: Purpose: Limited number of studies investigated the effects of Electrostatic powder paints (EPP) on human health. We investigated the effects of EPP exposure on lung function, exercise capacity, and quality of life, and the factors determining exercise capacity in EPP workers. Methods: Fifty-four male EPP workers and 54 age-matched healthy male individuals (control group) were included. Lung function and respiratory muscle strength were measured. The lower limit of normal (LLN) cut-points for FEV1 and FEV1 /FVC were calculated. An EPT was used to evaluate bronchial hyperactivity. The handgrip and quadriceps muscle strength were evaluated using a hand-held dynamometer. An ISWT was used to determine exercise capacity. The physical activity level was questioned using the IPAQ. The SGRQ and NHP were used to assessing respiratory specific and general quality of life, respectively. Results: Duration of work, FEV1, MIP, handgrip strength, and ISWT distance were significantly lower, and the change in FEV1 after EPT and %HRmax were significantly higher in the EPP group compared to the control group ( p < 0.05). There were no subjects with a < LLN for FEV1 and FEV1 /FVC in both groups. In the EPP group, ISWT distance was significantly related to age, height, duration of work, FEV1, change in FEV1 after EPT, MIP, MEP, handgrip strength, IPAQ, SGRQ, and NHP total scores ( p < 0.05). The change in FEV1 after EPT, MIP, and duration of work explained % 62 of the variance in the ISWT distance ( p < 0.001). Conclusions: Changes in lung function based on LLN for the FEV1 and FEV1 /FVC were not clinically relevant in EPP workers. Exercise capacity is impaired in EPP workers. Degree of exercise-induced bronchospasm, inspiratory muscle strength, and duration of work are the determinants of exercise capacity in EPP workers.